"I thought we were supposed to learn how to become better coaches": developing coach education through action research. Issue 3 (26th May 2020) - Voldby, Christian Røj; Klein-Døssing, Rasmus
ABSTRACT: Youth coaches play a crucial role in the development of young athletes and their physical, psychological and social well-being. Therefore, it is important to foster and develop youth coaches' ability to govern and act effectively in their coaching practices. Sports organisations facilitate the development of youth coaches through formal coach education. However, research has shown this to be with limited effect. The purpose of this action research study was to involve youth coaches in developing a new and more effective coach education practice. The coaches developed their practices through both dialogue and reflection with each other. A shift in the mindset of the coaches resulted in a more reflective and analytical approach in their way of thinking and talking about their practices. The most effective tools for improving the coach educational practice was the active management of the relations between the participating coaches and assisting the coaches' reflection and dialogue through the use of scaffolding. In order to engage coaches in the educational practice, alignment between coaches' expectations and both course content and form was crucial. These findings provide further insight into how coaches can develop their practices and how sports organisations can develop more effective coach education practices.